The influence of clinical and laboratory factors on the formation of monopronucleated zygotes after intracytoplasmic sperm injection (ICSI). Issue 2 (25th February 2019) - Fabozzi, Gemma; Rega, Emilia; Starita, Maria Flavia; Amendola, Maria Giulia; Colicchia, Antonio; Giannini, Pierluigi; Piscitelli, Claudio
Summary: The aim of the present study was to determine whether clinical or laboratory factors can influence the development of single pronucleated zygotes (1PN) and two polar bodies (PB) after ICSI. In total, 341 ICSI cycles performed at FertiClinic-Villa Margherita from January 2012 to December 2014 were enrolled in the study. Group A included 240 cycles with no 1PN−2PB while group B included 101 cycles with one or more 1PN−2PB. Age, stimulation protocol, infertility factor, amount of gonadotropin administered, duration of therapy, peak estradiol levels, number of follicles at maturation triggering, oocytes retrieved and mature oocytes, time between retrieval and injection and sperm characteristics were compared between groups. In opposition to previous results showing no relationship between 1PN occurrence and clinical or laboratory variables, we observed that 1PN−2PB zygote formation seems to be associated with a lower female age, higher level of E2 and higher number of follicles on day of oocyte maturation triggering, higher number of astenozoospermic male patients, more oocytes retrieved at pick-up, more mature oocytes (MII) and longer time to injection.